A study of clinical implementation of ventricular septal defect closure using three transthoracic approaches - Cai, Longren; Zeng, Ganhua; Li, Yan; Peng, Xinghua (American journal of translational research, 2021)
To investigate the clinical implementation of ventricular septal defect closure using the three transthoracic approaches.OBJECTIVETo investigate the clinical implementation of ventricular septal defect closure using the three transthoracic approaches.A total of 70 children with septal defects admitted to our hospital from January 2017 to December 2020 were selected as the study subjects. Among them, 10 children with the left thorax-right ventricle-left ventricle approach were assigned to Group A, 8 children with the right thorax-atrium dextrum-right ventricle-left ventricle approach were assigned to Group B, and 52 children with the subxyphoid-right ventricle-left ventricle approach were assigned to Group C. The surgical indices were recorded, the success rates of closure and cardiopulmonary function indices were compared, electrocardiogram (ECG), echocardiogram and X-ray film were investigated at 1, 3 and 12 months after surgery, and the incidence of complications was recorded.METHODSA total of 70 children with septal defects admitted to our hospital from January 2017 to December 2020 were selected as the study subjects. Among them, 10 children with the left thorax-right ventricle-left ventricle approach were assigned to Group A, 8 children with the right thorax-atrium dextrum-right ventricle-left ventricle approach were assigned to Group B, and 52 children with the subxyphoid-right ventricle-left ventricle approach were assigned to Group C. The surgical indices were recorded, the success rates of closure and cardiopulmonary function indices were compared, electrocardiogram (ECG), echocardiogram and X-ray film were investigated at 1, 3 and 12 months after surgery, and the incidence of complications was recorded.There was no statistically significant difference in the success rate of closure among the three groups (P > 0.05). The duration of intracardiac operations in Groups A and C was remarkably shorter than that in Group B, and the duration of skin incision and suture and hospital stay in Groups A and B were noticeably shorter than those in Group C (P < 0.05). After surgery, there was statistically significant difference in the contents of creatine kinase MB (CK-MB) isoenzyme, lactate dehydrogenase (LDH), serum malondialdehyde (MDA) and superoxide dismutase (SOD) among the three groups (P > 0.05). Airway resistance (Raw), oxygenation index (OI), and alveolar-arterial oxygen gradient (AaDO2) indicated that the postoperative pulmonary function in Group C was more effectively protected. There was no statistically significant difference in the incidence of complications among the three groups (P > 0.05).RESULTSThere was no statistically significant difference in the success rate of closure among the three groups (P > 0.05). The duration of intracardiac operations in Groups A and C was remarkably shorter than that in Group B, and the duration of skin incision and suture and hospital stay in Groups A and B were noticeably shorter than those in Group C (P < 0.05). After surgery, there was statistically significant difference in the contents of creatine kinase MB (CK-MB) isoenzyme, lactate dehydrogenase (LDH), serum malondialdehyde (MDA) and superoxide dismutase (SOD) among the three groups (P > 0.05). Airway resistance (Raw), oxygenation index (OI), and alveolar-arterial oxygen gradient (AaDO2) indicated that the postoperative pulmonary function in Group C was more effectively protected. There was no statistically significant difference in the incidence of complications among the three groups (P > 0.05).Ventricular septal defect closure using the three transthoracic approaches exhibited a high success rate and a high safety profile.CONCLUSIONVentricular septal defect closure using the three transthoracic approaches exhibited a high success rate and a high safety profile.